TATALAKSANA TETANUS GENERALISATA GRADE III YANG DISERTAI DENGAN COMMUNITY ACQUIRED PNEUMONIA DI RUANG PERAWATAN INTENSIF (LAPORAN KASUS) - Nasution, Nur Intan; Sobaryati (E-Journal Widya Kesehatan dan Lingkungan, 2020)
Tetanus is an acute toxemia due to neurotoxins produced by Clostridium tetani characterized by periodic and severe muscle rigidity and spasme, which threatens life and is world health problem. Goals of tetanus management include: (1) neutralization of unbound toxin; (2) eradication of tetanospasmin source; (3) muscle spasm control and treatment of autonomic dysfunction; and (4) general supportive management. The purpose of this paper is to report and describe the successful management of tetanus with complications due to muscle spasm, autonomic dysfunction and respiratory failure in intensive care unit. The method used is case report with retrospective approach and analyzed descriptively. Male, 34 years old, was admitted with complaints of wholebody rigidity 1 day before admission accompanied with trismus, dysphagia, hypertension, tachycardia, risus sardonikus, opistotonus and spasm of all muscles. Patient was diagnosed with tetanus generalisata grade 3 and admitted for 18 days in intensive care unit using mechanical ventilation. Tracheostomy was performed on the sixth day. The patient was fully recovered and discharged after 35 days of hospitalization. It can be concluded that tetanus mortality rate remains high because of its complications and longterm care for critical illness. Immediate diagnosis, identification of complications, complication management, and quality of supportive management are keys in determining outcome.